Transcatheter Aortic Valve Implantation: First Case in Nepal. - Adhikari, Chandra Mani; Bogati, Amrit; Roka, Madhu; Timalsina, Birat Krishna; Khan, Barkadin; Karki, Shova; Acharya, Anjana; Ghimire, Vijay; Shahi, Roshni; Prajapati, Dipanker; Rajbhandari, Sujeeb (Nepalese Heart Journal, 2022)
Surgical aortic valve replacement has remained the gold standard therapy for symptomatic severe aortic stenosis patients for decades. However, in past decade transcatheter aortic valve implantation has been an alternative to surgical aortic valve replacement in patients with symptomatic severe aortic stenosis who are not suitable for open heart surgery. We report first case of transcatheter aortic valve implantation in Nepal in an 80-year-old female with symptomatic severe AS who was successfully treated and had good functional and hemodynamic results at one-months follow-up.